Chorological analysis of species of the genus Dianthus in the South Caucasus region with an emphasis on the flora of Nakhchivan Autonomous Republic - Enzala Novruzova (Наукові горизонти)
The purpose of the study was to conduct a chorological analysis of six species of the genus Dianthus in the Nakhchivan Autonomous Republic, using field and molecular genetic methods. The main focus was on their geographical distribution, population status, and genetic diversity. As a result of the study of six species of the genus Dianthus, significant differences were found in their geographical distribution, ecological niches, and adaptation to local conditions. Molecular genetic analysis showed a high level of genetic diversity among populations of Dianthus nahcivanensis and Dianthus nakhchivanicus, which confirmed their uniqueness and endemic status. It has also been proven that the genus Dianthus has a high species diversity and shows significant variations in its distribution depending on the geographical and climatic conditions of the region. The study used geobotanic methods to determine the habitats of species and analyse factors affecting their distribution. In particular, features of the habitat were identified in connection with the local conditions of the Nakhchivan Autonomous Republic, which included a significant number of endemic species. The genetic analysis performed using the polymerase chain reaction method and sequencing helped to identify the level of genetic diversity and establish phylogenetic relationships between populations. It was found that Dianthus raddeanus, Dianthus parviflorus, Dianthus nakhchivanicus and Dianthus nahcivanensis species are more vulnerable due to the impact of anthropogenic activities, in particular agriculture and grazing, which has led to a decrease in the area of their habitat. Modelling using the maximum entropy method showed potential zones of expansion of species habitats under favourable ecological conditions. The results obtained were important for understanding the ecological patterns of distribution of the genus Dianthus in the region and the development of strategies for preserving biodiversity in the face of climate change and anthropogenic pressure. Based on the study, it was recommended to create or expand protected areas, limit anthropogenic impact, and conduct additional monitoring of the number and genetic structure of Dianthus populations